A tale of two boys: case report on non-consanguineous siblings with cerebral palsy. - Leelavathi M; Lim, JL; Ahmad S (Penerbit UKM, 2014)
Cerebral palsy is a common cause of childhood disability. It has a great impact on parents and caregivers, especially when it reoccurs in the same family. Although familial cerebral palsy is relatively uncommon, cases have been reported among children from consanguineous, non-consanguineous marriages and multiple pregnancies suggesting a possible complex genetic mode of inheritance. Physicians need to be aware of the possibility of familial cerebral palsy for early detection and counseling. We describe a rare case of two male siblings from a non-consanguineous marriage affected by cerebral palsy.